Aktivitas Penghambatan Ekstrak Etanol Biji Asam Gelugur (Garnicia atroviridis) terhadap Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus - Haris Muntaha; Sunardi Sunardi; Ngatirah Ngatirah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to determine the inhibitory activity of ethanol extract from tamarind seeds against the growth of Escherichia coli and Staphylococcus aureus bacteria at various concentrations. This study used a randomized complete block design with 1 factor, namely the concentration of tamarind seed extract with 6 levels, namely A1 (0.5%), A2 (1%), A3 (1.5%), A4 (2%), A5 (2.5%), A6 (3%). Each treatment was repeated 3 times. Research evaluation includes qualitative phytochemical tests and antioxidant activity against ethanol extract of gelugur acid seeds and bacterial inhibition. The results showed that in the ethanol extract of tamarind seeds there are phytochemical compounds which include flavonoids, saponins, tannins, and terpenoids. And has antioxidant activity of IC 50 = 15.77 ppm. Tamarind seed extract affects the growth of Escherichia coli and Staphylococcus aureus bacteria. The minimum concentration of ethanol extract of tamarind seeds that can inhibit Escherichia coli and Staphylococcus aureus bacteria is 0.5% with inhibitory zones of 15.6 mm and 10.9 mm respectively.